(untitled) (Global Journal of Medical Research, 2023)
Introduction The review is motivated by COVID-19 vaccination poisoning paths in human hosts from a sebaceous immunobiological perspective purposed to facilitate pharmacokinetic targeting solutions Review The review evaluates the sebaceous immunobiological chain in the downstream and upstream human physiology It is incentivized by the lipoprotein correlations to COVID-19 severity in human hosts and it considers the post-vaccination risk factors and neuronal infection paths The review is guided by the generation pathways of reactive oxygen species